Life Cycle Collection Management - Shenton, Helen (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
Life cycle collection management is a way of taking a long-term approach to the responsible stewardship of the British Library's collections and is one of the Library's strategic strands. It defines the different stages in a collection item's existence over time. These stages range from selection and acquisitions processing, cataloguing and press marking, through to preventive conservation, storage and retrieval. Life cycle collection management seeks to identify the costs of each stage in order to show the economic interdependencies between the phases over time. It thereby aims to demonstrate the long-term consequences of what the library takes into its collections, by making explicit the financial and other implications of decisions made at the beginning of the life cycle for the next 100 plus years. This paper describes the work over the past year at the British Library on this complex and complicated subject. It presents the emerging findings and suggests how it can be used for practical reasons (by individual curators and selectors) and for economic, governance and political purposes. The paper describes the next steps in the project, for example, on a predictive data model. The British Library is seeking to benchmark itself against comparable organisations in this area. It intends to work with others on specific comparison for example, of life cycle costing of electronic and paper journals, as a prelude to eliding digital and 'traditional' formats.